"Your Skin's Not as Good as Us": Microaggressions among Transracially-Adopted Children from China. Issue 4 (2nd October 2019) - Zhang, Emily; Zhang, Xian; Pinderhughes, Ellen E.
Abstract: This mixed methods study examined the nature of adoption and racial microaggressions and their relations with age and community diversity among 42 Chinese transracial adoptees ages 5–9. Using microaggression typologies by Baden and Sue et al., we found that children must often navigate multiple messages within a single microaggression incident. Although experience and awareness of microaggressions did not differ among children by community diversity, experience of racial microaggression incidents was positively associated with age. Given that young children experience microaggressions, preparation for bias should be considered for children at young ages in a developmentally appropriate manner.